Strategi Pengembangan Usaha Ternak Sapi Potong Di Distrik Sarmi Timur Kabupaten Sarmi Provinsi Papua - Kornelius Liat Nuhon; Ristasari Sadi; Dortje Janet Kondong (STIPER Santo Thomas Aquinas Jayapura, 2026)
The main objective of this research is to analyze internal and external factors and determine a strategy for developing beef cattle businesses in Sarmi District, Sarmi Regency, Papua Province. The method used in this research is the survey method. Data collection was carried out by observation and direct interviews with respondents. The selection of respondents was carried out purposively. Data were analyzed using Internal Factor Evaluation (IFE), External Factor Evaluation (EFE) and to obtain development strategies analyzed using SWOT. The research results showed that there were 3 strength factors, 3 weakness factors, 6 opportunity factors and 3 threat factors. The results of the research show that the strategy that can be applied in developing the beef cattle business in Sarmi District, Sarmi Regency, Papua Province is optimizing and developing the internal capabilities of breeders and utilizing available natural resources, providing mentoring and counseling programs accompanied by demonstrations so that they can increase the ability of breeders, establish business partnership with the government to take advantage of market opportunities, introduction of agricultural waste-based feed processing technology that is adapted to local regional conditions, collaboration with the local government to make livestock businesses more effective, provision of infrastructure to support livestock businesses.